HASIL KEGIATAN PENGABDIAN KEPADA MASYARAKAT MELALUI PROGRAM PENGEMBANGAN MASYARAKAT DI DESA BERNGAM KEC. BINJAI KOTA, KOTA BINJAI - Hotmaida Simanjuntak; Yosephine Aprilia L. Tobing; Reky Hoklae Aldo Siagian; Anastasiah Sibarani; Grace Indryani Pasaribu (Kreativitas Pada Pengabdian Masyarakat (Krepa), 2025)
This service discusses the Results of Community Service Activities Through Community Development Programs in Berngam Village, Binjai City District, Binjai City. This activity not only focuses on sharing knowledge, but also becomes a means of community empowerment through mutual cooperation activities in Berngam Village. In addition, this program is designed to strengthen the relationship between the world of education and community needs, especially in facing various challenges related to environmental health in the modern era. How to implement the activities of Socialization and Counseling, Training and Workshops, Mutual Cooperation, Religious and Cultural Activities, and Infrastructure Development. With the results of the Knowledge and Awareness Improvement activities, PkM participants gain broader insights into the importance of mutual cooperation and cooperation with Berngam Village residents in various social activities, Increased Environmental Awareness The community increasingly understands the importance of maintaining environmental cleanliness, Effective Collaboration and Partnerships, Interaction with Various Community Groups PkM participants participate in other religious activities.